Powerful and Powerless Language Usage Between Genders: A Case Study Among Lecturers - Bin Mohd Salim, Mohd Nur Fitri; Haji Mohamad Yusuf, Asmahanim Binti; Binti Wan Mustapha, Wan Zumusni; Binti Ahmad, Irma; Ashahri Bin Mohd Salim, Mohamad Safwat (KnE Social Sciences, 2019)
This study investigates the gender language used in workplace; specifically, on the comparison and exploration of power language between male and female lecturers who are teaching in the education field. In the effort to answer whether the general opinion that man includes more power language in their speech compared to woman; equal numbers of participants are chosen from both genders and several observations of teaching and learning sessions initiated by the participants in their respective classes were conducted by the researchers. The language used by all participants was analyzed based on the use of two language expressions; directives and elicitations. The results of the findings suggest that male lecturers used more directives and elicitations; with Male Lecturer A, who used a total of 27% power languages and Male Lecturer B, who used a total of 35% power languages. The power language used by the female lecturers are relatively less than male lecturers; with both female lecturers: Female Lecturer A and B each using a total of 19% power languages in their speech. Therefore, the study shows that male uses more power language than women. However, this study also indicates that the use of their power language also depends on the context of their language usage. Keywords: powerful language, powerless language, gender language, dominance theory, interactive positioning